2022
DOI: 10.1101/2022.02.24.481783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methionine Metabolism Controls the B-cell EBV Epigenome and Viral Latency

Abstract: Epstein-Barr virus (EBV) subverts host epigenetic pathways to switch between viral latency programs, colonize the B-cell compartment and reactivate. Within memory B-cells, the reservoir for lifelong infection, EBV genomic DNA and histone methylation marks restrict gene expression. But, this epigenetic strategy also enables EBV-infected tumors, including Burkitt lymphomas to evade immune detection. Little is known about host cell metabolic pathways that support EBV epigenome landscapes. We therefore used amino … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…In addition to DNA methylation, histone epigenetic marks strongly contribute to EBV latency gene expression. 14,21,[49][50][51][52][53][54][55][56] We therefore next profiled GC cytokine effects on the LMP1 promoter. Since previous studies identified three LMP1 promoter sites occupied by STAT factors 57 We next characterized IL-21 epigenetic effects on the LMP1 promoter in latency I Bcells, given the observation that IL-21 strongly activates STAT3 phosphorylation and derepresses LMP1 expression, whereas other GC cytokine stimuli did so comparatively weakly.…”
Section: Gc Cytokine Effects On Lmp1 Promoter Histone Epigenetic Marksmentioning
confidence: 99%
“…In addition to DNA methylation, histone epigenetic marks strongly contribute to EBV latency gene expression. 14,21,[49][50][51][52][53][54][55][56] We therefore next profiled GC cytokine effects on the LMP1 promoter. Since previous studies identified three LMP1 promoter sites occupied by STAT factors 57 We next characterized IL-21 epigenetic effects on the LMP1 promoter in latency I Bcells, given the observation that IL-21 strongly activates STAT3 phosphorylation and derepresses LMP1 expression, whereas other GC cytokine stimuli did so comparatively weakly.…”
Section: Gc Cytokine Effects On Lmp1 Promoter Histone Epigenetic Marksmentioning
confidence: 99%